Trastornos de atracción sexual hacia animales: Clasificación diagnóstica basada en una revisión sistemática - Ferrari, Mónica; Revollo, Alicia; Cuellar, Jésica; Manzanelli, Fernanda; Valdi, Ana Lía; Reyes Plazaola, Paola; Díaz Videla, Marcos (Revista de Psicopatología y Psicología Clínica, 2020)
Sexual attraction towards animals disorder: Diagnostic classification based on a systematic review Abstract: Sexual intercourse between humans and animals has existed since the dawn of humanity in every place and culture of the world. Nevertheless, this issue has been scarcely approached by science. Given the wide differences in behavior and preferences among people who practice sex with animals, it is necessary to establish a subtypes classification. For this purpose, a systematic review of investigations was carried out that allowed us to select 26 empirical studies. Their analysis permitted to describe the group of Sexual Attraction Towards Animals disorder, comprising four differentiated disorders: (1) zoophilic disorder, (2) bestiality disorder, (3) sexual zoosadism, and (4) sexual attraction disorder towards animals due to medical or substance-induced illness. Additionally, the diagnostic criteria for each are proposed. Implications and limitations are discussed, as well as the value of having a classification of these disorders and the need to incorporate their study in the academic field. Keywords: Bestiality; disorders; paraphilias; zoophilia; zoosadism. Resumen: Las relaciones sexuales entre humanos y animales han existido desde los albores de la humanidad en todos los lugares y culturas del mundo. Sin embargo, han sido abordadas escasamente por la ciencia. Dadas las amplias diferencias en las conductas y preferencias entre quienes practican sexo con animales, se hace necesario establecer una clasificación de subtipos. Con ese propósito, se realizó una revisión sistemática de investigaciones que arrojó 26 estudios empíricos. El análisis de estos permitió describir el grupo de Trastornos por atracción sexual hacia animales, comprendiendo cuatro trastornos diferenciados: (1) trastorno zoofílico, (2) trastorno por bestialidad, (3) zoosadismo sexual, y (4) trastorno por atracción sexual hacia los animales debido a enfermedad médica o inducido por sustancias. Adicionalmente, se propusieron criterios diagnósticos para cada uno. Se discuten las implicancias y limitaciones, el valor de contar una clasificación de estos trastornos y la necesidad de incorporar su estudio en el ámbito académico. Palabras clave: Bestialismo; parafilias; trastornos; zoofilia; zoosadismo.